ISAN DURING THE SEVENTH REIGN IN THE EYES OF H.R.H. PRINCE PARIBATRA (BORIPHAT) - JUMBALA , PRUDHISAN (Journal of Suan Sunandha Arts and Culture, 2023)
This article summarizes and analyzes H.R.H. Prince Paribatra, the Prince of Nagara Svarga’s report on his inspection tour of Isan (Northeast Siam) in 1926 during the Seventh Reign (1925-1935). The findings are that, although the prince went there as Minister of Defense, he has foremost in his mind his duty as a Supreme Councillor. Thus, he organized the report so as to be of benefit to the various ministries as well as to suggest ways of in regarding their duties. The report is a relatively rare source of information on the life and livelihood of both ruralites and townspeople in Isan. It highlighted the fact that, as air and rail means of transportation made inroads, there were distinct signs of the people’s readiness to shift from self-sufficient economy to market economy. Also, greater educational provision would lead to changes in attitudes from one of subservience to one ever more aware of rights and freedoms. Thus, government officers needed to adjust their stance from issuing orders to allowing participation and seeking cooperation from the locals.